Translating knowledge about abiotic stress tolerance to breeding programmes. (8th February 2017) - Gilliham, Matthew; Able, Jason A.; Roy, Stuart J.
Summary: Plant breeding and improvements in agronomic practice are making a consistent contribution to increasing global crop production year upon year. However, the rate of yield improvement currently lags behind the targets set to produce enough food to meet the demands of the predicted global population in 2050. Furthermore, crops that are exposed to harmful abiotic environmental factors (abiotic stresses, e.g. water limitation, salinity, extreme temperature) are prone to reduced yields. Here, we briefly describe the processes undertaken in conventional breeding programmes, which are usually designed to improve yields in near‐optimal conditions rather than specifically breeding for improved crop yield stability under stressed conditions. While there is extensive fundamental research activity that examines mechanisms of plant stress tolerance, there are few examples that apply this research to improving commercial crop yields. There are notable exceptions, and we highlight some of these to demonstrate the magnitude of yield gains that could be made by translating agronomic, phenological and genetic solutions focused on improving or mitigating the effect of abiotic stress in the field; in particular, we focus on improvements in crop water‐use efficiency and salinity tolerance. We speculate upon the reasons for the disconnect between research and research translation. We conclude that to realise untapped rapid gains towards food security targets new funding structures need to be embraced. Such funding needs to serve both the core and collaborative activities of the fundamental, pre‐breeding and breeding research communities in order to expedite the translation of innovative research into the fields of primary producers. Significance statement: Abiotic stress routinely reduces the yield of all our major crops. However, most crop‐breeding programs do not specifically target improved abiotic stress tolerance. In this review we highlight how breeding for abiotic stress tolerance can improve crop productivity. We discuss barriers to research translation and propose that funding structures that serve both fundamental research and breeding are needed to meet food security goals in the face of a changing climate.